Influence of family type and parenting behaviours on teenage sexual behaviour and conceptions. Issue 6 (12th May 2006) - Bonell, C; Allen, E; Strange, V; Oakley, A; Copas, A; Johnson, A; Stephenson, J
Abstract : Background: Longitudinal data were used to explore relations between teenage pregnancy, sexual behaviour, and family type. The study examined whether students from lone parent and/or teenage mother initiated families more commonly report sex, lack of contraception at first sex, and/or conceptions by age 15/16, and whether such associations can be explained by low parental strictness, difficult parent-child communication, and/or low parental input into sex education. Up to date longitudinal UK research on family influences on conceptions is lacking, as is longitudinal research on family influences on sexual behaviour. No previous studies have comprehensively examined effects of parenting behaviours. Unlike previous research, this study tested theories suggesting that parenting deficits among lone parent and teenage initiated families increase risk of teenage pregnancy among their children. Methods: Secondary analysis of data from a trial of sex education. Results: Girls and boys from lone parent families or having mothers who were teenagers when they were born were more likely to report sex but not lack of contraception at first sex by age 15/16. Girls and boys with mothers having them as teenagers, and boys but not girls from lone parent families, were more likely to report being involved in conceptions by age 15/16. Only the association between teenage mother family and girls' conceptions was reduced by adjusting for a parenting behaviour measure. Conclusions: Students from lone parent families or having mothers who were teenagers when they were born are more likely to report early sexual debut and conceptions by age 15/16, but this is not generally explained by parenting style.